Analysis of Annual Costs of Mobile Clinics in the Southern United States - Sharon Attipoe-Dorcoo; Rigoberto Delgado; Dejian Lai; Aditi Gupta; Stephen Linder (SAGE Publishing, 2020)
Introduction Mobile clinics provide an efficient manner for delivering healthcare services to at-risk populations, and there is a need to understand their economics. This study analyzes the costs of operating selected mobile clinic programs representing service categories in dental, dental/preventive, preventive care, primary care/preventive, and mammography/primary care/preventive. Methods The methodology included a self-reported survey of 96 mobile clinic programs operating in Texas, North Carolina, Georgia, and Florida; these states did not expand Medicaid and have a large proportion of uninsured individuals. Data were collected over an 8-month period from November 2016 to July 2017. The cost analyses were conducted in 2018, and were analyzed from the provider perspective. The average annual estimated costs; as well the costs per patient in each mobile clinic program within different service delivery types were assessed. Costs reported in the study survey were classified into recurrent direct costs and capital costs. Results Results indicate that mean operating costs range from about $300 000 to $2.5 million with costs increasing from mammography/primary care/preventive delivery to dental/preventive. The majority of mobile clinics provided dental care followed by dental/preventive. The cost per patient visit for all mobile clinic service types ranged from $65 to $529, and appears to be considerably less than those reported in the literature for fixed clinic services. Conclusion The overall costs of all delivery types in mobile clinics were lower than the costs of providing care to Medicare beneficiaries in federally funded health centers, making mobile clinics a sound economic complement to stationary healthcare facilities.